Role of the plasma scale length in the harmonic generation from solid targets - Zepf, M; Tsakiris, G; Pretzler, G; Watts, I; Chambers, D; Norreys, P; Andiel, U; Dangor, A; Eidmann, K; Gahn, C; Machacek, A; Wark, J; et al. (1998)
We have investigated the generation of high harmonics from the interaction of 150 fsec, 790 nm, and 395 nm laser pulses with solid targets. Experiments are presented that demonstrate a strong dependence of the conversion efficiency on the temporal pulse shape and the resulting density scale length (L/λ) of the preformed plasma. The highest conversion efficiencies are achieved for short density scale lengths (L/λ ≤ 0.4), which result from high contrast ratio pulse interactions.